2016
DOI: 10.1016/j.jprot.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic labeling approach for glycoproteomic analysis reveals altered glycoprotein expression upon GALNT3 knockdown in ovarian cancer cells

Abstract: Epithelial ovarian cancer (EOC) is a disease responsible for more deaths among women in the Western world than all other gynecologic malignancies. There is urgent need for new therapeutic targets and a better understanding of EOC initiation and progression. We have previously identified the polypeptide N-acetylgalactosaminyltransferase 3 (GALNT3) gene, a member of the GalNAc-transferases (GalNAc-Ts) gene family, as hypomethylated and overexpressed in high-grade serous EOC tumors, compared to low malignant pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…We have previously identified the GalNAc-T3 (GALNT3) gene as a potential EOC oncogene, highly expressed in advanced disease, as GALNT3 expression was significantly associated with poor outcome (15). We also demonstrated that in EOC cells, GALNT3 might directly alter biosynthesis and/or aberrant glycosylation of different O-glycoproteins that could play an essential role in EOC dissemination (15)(16)(17). However, to date, no other studies have comprehensively assessed the implications of other members of the GalNAc-Ts gene family in EOC dissemination.…”
Section: Altered Expression Of Different Galnac-transferases Is Assocmentioning
confidence: 99%
“…We have previously identified the GalNAc-T3 (GALNT3) gene as a potential EOC oncogene, highly expressed in advanced disease, as GALNT3 expression was significantly associated with poor outcome (15). We also demonstrated that in EOC cells, GALNT3 might directly alter biosynthesis and/or aberrant glycosylation of different O-glycoproteins that could play an essential role in EOC dissemination (15)(16)(17). However, to date, no other studies have comprehensively assessed the implications of other members of the GalNAc-Ts gene family in EOC dissemination.…”
Section: Altered Expression Of Different Galnac-transferases Is Assocmentioning
confidence: 99%
“…Despite treatment improvements, long-term survival rates for patients with advanced disease remain disappointing [3]. EOC lethality primarily stems from the inability to detect the disease at an early, organ-confined stage, and the lack of effective therapies for advanced-stage disease (e.g., metastasis) [4]. Indeed, despite advances in cytotoxic therapies [5,6], only 30% of patients with advanced-stage EOC survive 5 years after initial diagnosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…One way to resolve this problem is to target metastasis-specific pathways with novel therapies. Hence, focused identification of novel prometastatic EOC pathways and molecules could improve the chances of discovering new and more effective EOC therapies [4].…”
Section: Introductionmentioning
confidence: 99%
“… This article contains raw and processed data related to research published in “ Role of the polypeptide N-acetylgalactosaminyltransferase 3 in ovarian cancer progression: possible implications in abnormal mucin O-glycosylation ” [1] . The data presented here was obtained with the application of a bioorthogonal chemical reporter strategy analyzing differential glycoprotein expression following the knock-down (KD) of the GALNT3 gene in the epithelial ovarian cancer (EOC) cell line A2780s.…”
mentioning
confidence: 99%